2021
DOI: 10.3390/rs13050952
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Reinforcement Conditions in Concrete Structures by GPR, Impact-Echo Method and Metal Magnetic Memory Method

Abstract: It is important to use adequately reliable non-destructive methods that would be capable of determining the reinforcement conditions in concrete structures. Three different methods: ground penetrating radar, impact-echo method, and metal magnetic memory method were used for testing laboratory-prepared reinforced concrete beams (with a reinforcing bar of the same diameter along its whole length, reinforcing bar locally impaired, and reinforcing bar interrupted). The ground-penetrating radar proved the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…However, it can only measure pre-defined sampling positions and cannot quantitatively detect minor defects. Other NDT technologies, such as impact-echo (IE) [12], electrical resistivity (ER) [13], and GPR, are often used in the applications of subsurface transportation infrastructure inspection. Among these technologies, GPR is currently the best choice for airport runway inspection since it can achieve fast and full coverage detection with high resolution and good coverage in range and depth.…”
Section: Related Workmentioning
confidence: 99%
“…However, it can only measure pre-defined sampling positions and cannot quantitatively detect minor defects. Other NDT technologies, such as impact-echo (IE) [12], electrical resistivity (ER) [13], and GPR, are often used in the applications of subsurface transportation infrastructure inspection. Among these technologies, GPR is currently the best choice for airport runway inspection since it can achieve fast and full coverage detection with high resolution and good coverage in range and depth.…”
Section: Related Workmentioning
confidence: 99%
“…Studies have shown that steel damage or fracture affects the predominant frequency. Therefore, in the finite element simulation, the influence of the steel bar on the model needs to be considered [9]. Kee, S.H., et al proposed in their study that the water or harmful materials in concrete causes various durability problems by reducing the stiffness of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The foundation of MMM detection lies in the Self-Magnetic Flux Leakage (SMFL) effect [11], which refers to local magnetic field changes inside magnetic materials without an external magnetic field due to defects or stress concentrations [12][13][14]. MMM detection determines defects in structures by measuring the SMFL field changes of ferromagnetic materials, and it is suitable for detecting microscopic defects [15,16], making it widely applied in fields such as pipeline transportation, power facilities, and industrial manufacturing [17][18][19].…”
Section: Introductionmentioning
confidence: 99%